Philippines : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper assesses potential spillover effects to the Philippines from US policy shifts and lower growth in China. The US fiscal expansion affects the Philippine economy through the interest rate and the trade channels. The net spillover impact on Philippine GDP is negative in the short term. Compared with the productive case, in which the net output impact is positive, the US nominal policy rate rises by less, but faster normalization of the US term premium leads to higher real interest rates. On the other hand, the gain from trade is smaller owing to the weaker domestic demand expansion in the United States.